Impact of Entrepreneurship and Globalization on Environment in Developed Countries: Environmental Kuznets Curve Approach - Lotfi Mekhzoumi; Feyrouz Zerroukhi; Ahmed R. El Wawi (Journal of North African Economies, 2025)
Using the Environmental Kuznets hypothesis (EKC), this paper seeks to investigate the impact of entrepreneurship and globalization on CO2 emissions. Using static panel data methodology, this research provides the evaluation of EKC specifications for nineteen developed countries from 2001 to 2019. The estimation results of the Feasible Generalized Least Squares (FGLS) model and the Panel Corrected Standard Error (PCSE) model generated the same result as the validity of the EKC hypothesis, indicating that environmental pollution is associated with the economic growth in an inverted N-letter shape, taking into account entrepreneurship and globalization. Entrepreneurship increases CO2 emissions in developed countries, whereas globalization has a beneficial impact on the environment.